Analysis of Boron Neutron Capture Therapy Dose Rate for Head and Neck Rhabdomyosarcoma Cancer in a 10-Year-Old Child Phantom - E. Hidayanto; F. M. Salim; W. S. Budi; F. Arianto (Atom Indonesia, 2026)
Rhabdomyosarcoma is a malignant cancer that affects soft tissues and predominantly occurs in children. Approximately 35–40% of cases occur in the head and neck region. Boron Neutron Capture Therapy (BNCT) has been employed in the treatment of head and neck cancers and has shown promising results. However, neutron, proton, and gamma-ray scattering pose significant challenges, as they contribute to the total BNCT dose. This study aims to analyze the BNCT dose received by a 10-year-old child phantom. The method involves simulating an ORNL-MIRD head and neck phantom of a 10-year-old child irradiated with BNCT using the Monte Carlo N-Particle (MCNP) version 6.2 code. The BNCT dose was determined by calculating the absorbed dose, and the simulation results were analyzed based on the deterministic effects on at-risk organs. The absorbed dose values for the skin, brain, spinal cord, and thyroid were 0.00641 Gy, 1.566 Gy, 0.710 Gy, and 0.018 Gy, respectively. The deterministic effects on the skin and thyroid were minimal, as the absorbed doses did not exceed their respective threshold limits.